ADVISORY COUNCIL ON SOCIAL SECURITY COMMITMENT TO CHANGE: FOUNDATIONS FOR REFORM PART 3 OF 3 (Tufts Archival Research Center, 2007)
Oversized; Pages Out of Order; Missing Page(s); Collection of proposals made to the Advisory Council on Social Security in December 1991. Reviews the recommendation specifications for reducing health care costs, increasing GNP growth, and reforming health care institutions. Estimates costs and savings of proposals. Provides prototype comprehensive plans.